Kinetics of Ag300 nanoclusters formation: The catalytically effective nucleus via a steady‐state approach. Issue 4 (16th January 2019) - Kytsya, Andriy; Bazylyak, Liliya; Simon, Paul; Zelenina, Iryna; Antonyshyn, Iryna
Abstract: The kinetics of formation of silver nanoparticles consisting of nearly 300 metal atoms is investigated, which were prepared by reduction of silver nitrate with hydrazine in ethylene glycol at 25°C without any stabilizer other than the glycol solvent. The resulting sigmoidal kinetic curves are analyzed by using the 1997 Finke–Watzky two‐step mechanism of slow continuous nucleation with subsequent fast autocatalytic surface growth. The kinetics of homogeneous nucleation of metal nanoparticles was analyzed using the assumption about the stepwise adjunction of precursor and the quasi steady‐state approximation. The equations were proposed to calculate the concentration of the formed metal nanoparticles and their mean size from the experimentally determined values of the Finke–Watzky rate constants. It is shown that a stepwise nucleation process can be described in the terms of the catalytically effective nucleus concept and that the number of atoms in the catalytically effective nucleus can be estimated.